2011
DOI: 10.1007/s12574-011-0086-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of plasma brain natriuretic peptide levels in untreated hypertensive patients

Abstract: LVMI and E velocity were independent determinants of plasma BNP level in patients with untreated hypertension. Plasma BNP level is substantially useful for the screening of abnormalities of LV geometry and/or function in patients with untreated hypertension. Additional echocardiography is useful to assess the mechanism of the elevation of plasma BNP level in untreated hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…Major findings in the current study are (1) subjects with LV diastolic dysfunction had a higher estimated LVFP and a higher prevalence of CH, which were not accompanied by elevated plasma BNP levels, than those without LV diastolic dysfunction; (2) both high estimated LVFP and low plasma BNP levels were independent factors associated with CH; and (3) CH with LV diastolic dysfunction predicted a poor prognosis. Unlike the well-known positive association between plasma BNP levels and LVH in HF patients and hypertension, 3 , 4 we found a negative association between plasma BNP levels and LVH in a subclinical population without heart disease, which might indicate a predisposition to diastolic dysfunction.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Major findings in the current study are (1) subjects with LV diastolic dysfunction had a higher estimated LVFP and a higher prevalence of CH, which were not accompanied by elevated plasma BNP levels, than those without LV diastolic dysfunction; (2) both high estimated LVFP and low plasma BNP levels were independent factors associated with CH; and (3) CH with LV diastolic dysfunction predicted a poor prognosis. Unlike the well-known positive association between plasma BNP levels and LVH in HF patients and hypertension, 3 , 4 we found a negative association between plasma BNP levels and LVH in a subclinical population without heart disease, which might indicate a predisposition to diastolic dysfunction.…”
Section: Discussioncontrasting
confidence: 99%
“…A positive correlation between high plasma BNP levels, LVH, and diastolic dysfunction has been demonstrated in patients with heart failure (HF) or hypertension. 3 , 4 Considering the cardiovascular protective properties of NPs, such as their natriuretic, vasodilative, antihypertrophic, and antifibrotic effects, NPs are believed to be compensatorily released to relieve hemodynamic stress.…”
mentioning
confidence: 99%
“…Cardiomyocytes secrete NPs into the systemic circulation in response to myocardial mechanical loading 2 ; thus, the elevation of plasma NP is essential to cardiac hypertrophy or failure 1 . Previous studies have shown that plasma BNP levels are well correlated with LVMI, that is, LV hypertrophy and LV diastolic function 27,28 . LV hypertrophy is an established independent risk factor for cardiovascular morbidity and mortality 29 .…”
Section: Discussionmentioning
confidence: 99%
“… 1 Previous studies have shown that plasma BNP levels are well correlated with LVMI, that is, LV hypertrophy and LV diastolic function. 27 , 28 LV hypertrophy is an established independent risk factor for cardiovascular morbidity and mortality. 29 However, LV concentric remodelling, defined as increased RWT and normal LVMI, is also associated with poorer prognoses compared with the normal LV geometry.…”
Section: Discussionmentioning
confidence: 99%
“…Strain echocardiography has provided quantification of regional myocardial systolic function objectively and is less influenced by tethering effects and cardiac translational artifact than Doppler tissue imaging [14]. Along with echocardiography, other examinations as electrocardiography (ECG), radiography, computed tomography, magnetic resonance imaging, measurement of serum cardiac biomarkers including C-reactive protein (CRP), N-terminal pro-B-type natriuretic peptide (nt-proBNP), troponin T (TnT), creatine kinase MB (CK-MB), and lactate dehydrogenase (LDH) are important diagnostic tools in the evaluation of cardiac function [1618]. Some reports have already shown differences between M-mode and strain parameters in Dox-cardiotoxicity models [19,20].…”
Section: Introductionmentioning
confidence: 99%